Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/molecules26164902
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Mechanism of Hydroxycamptothecin via the Metabolic Perturbation of Ribonucleotide and Deoxyribonucleotide in Human Colorectal Carcinoma Cells

Abstract: Hydroxycamptothecin (SN38) is a natural plant extract isolated from Camptotheca acuminate. It has a broad spectrum of anticancer activity through inhibition of DNA topoisomerase I, which could affect DNA synthesis and lead to DNA damage. Thus, the action of SN38 against cancers could inevitably affect endogenous levels of ribonucleotide (RNs) and deoxyribonucleotide (dRNs) that play critical roles in many biological processes, especially in DNA synthesis and repair. However, the exact impact of SN38 on RNs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…The CPT derivatives exhibit strong antitumor activity and low toxic adverse effects. Other marketed CPT derivatives, including hydroxylCPT and exatecan, have been tested in clinical trials and found to strongly block the effects of DNA synthesis in tumor cells 96 , 97 . Rubitecan, a second-generation topoisomerase inhibitor, is used to treat blood cancers and a variety of solid tumors 98 .…”
Section: Dna Damagementioning
confidence: 99%
“…The CPT derivatives exhibit strong antitumor activity and low toxic adverse effects. Other marketed CPT derivatives, including hydroxylCPT and exatecan, have been tested in clinical trials and found to strongly block the effects of DNA synthesis in tumor cells 96 , 97 . Rubitecan, a second-generation topoisomerase inhibitor, is used to treat blood cancers and a variety of solid tumors 98 .…”
Section: Dna Damagementioning
confidence: 99%